A Business Plan On Establishment of Corndog Station Phase 2 Package 2 Block 35 Lot 13, Bagong Silang Caloocan.: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Corndog Station was conceptualized on February 13, 2023. We have a great atmosphere anda variety of corndogs with interesting fillings. The goal of the company's marketing strategy isto diversify the flavor profiles of the corndogs it serves to its target market. New fillings areavailable at Corndog Station to satisfy our customers. Likewise, those who are eager to trysomething new. The business operates at Phase 2 Package 2 Block 35 Lot 13, Bagong SilangCaloocan. Perfectly established around the target market area where, which is adjacent toschools, condominiums, apartments, subdivisions, and Highways.Corndog Station will be focused on organizational structure, employee responsibilities, andcompany policies. It also discusses corporate social responsibility and business monitoring.Corndog Station will be unique in terms of the size of the corn dog. Our corn dogs will bebigger than normal corn dogs at the same time at an affordable price, and our sauce tastesextra spicy, cheesy, and sweet. Recognizing the target market is one of the most importantsteps in building a successful business. Therefore, Corndog Station has to identify and selecta target market so it can direct its marketing effort to that group of customers and better satisfytheir needs and wants.Corndog Station will create a good system that can be implemented inside our organization,and we will operate strategically as much as possible. We will use any kind of marketing plan,like posting on any social media platform, to promote our product and services. We also focuson Inventory control to ensure that we have enough units to fulfill orders and have safetystock. We will make sure that every part of this management has a knowledge of ourproduction and is willing to commit to our goals.
Keywords: Business